2017
DOI: 10.3390/metabo8010001
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Generates Numerous Artifacts during Sample Extraction and Storage of Extracts in Metabolomics Research

Abstract: Abstract:Many metabolomics studies use mixtures of (acidified) methanol and water for sample extraction. In the present study, we investigated if the extraction with methanol can result in artifacts. To this end, wheat leaves were extracted with mixtures of native and deuterium-labeled methanol and water, with or without 0.1% formic acid. Subsequently, the extracts were analyzed immediately or after storage at 10 • C, −20 • C or −80 • C with an HPLC-HESI-QExactive HF-Orbitrap instrument. Our results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…No information about the N ‐methylation of related drugs has been found. N ‐methylation of amines are common artefacts when working with methanolic solutions, particularly at elevated temperatures. In the present study, the compounds were dissolved in methanol and later incubated at a low final methanolic concentration level of 0.3%.…”
Section: Resultsmentioning
confidence: 99%
“…No information about the N ‐methylation of related drugs has been found. N ‐methylation of amines are common artefacts when working with methanolic solutions, particularly at elevated temperatures. In the present study, the compounds were dissolved in methanol and later incubated at a low final methanolic concentration level of 0.3%.…”
Section: Resultsmentioning
confidence: 99%
“…The reported that extraction of plant material by methanol can led to the artifacts containing methoxyl groups [12]. Since compound 1 contains a methoxyl group, we therefore change the solvent extraction of the plant material by using EtOAc.…”
Section: Resultsmentioning
confidence: 99%
“…In tomato, several extraction protocols using methanol-water (for polar/semi-polar metabolites, such as organic acids, carbohydrates, amino acids, quaternary ammonium compounds, and hydroxycinnamic acids), and/or chloroform (for a polar/nonpolar metabolites, such as carotenoids and fatty acids) [ 34 ], with variations in the relative amount of each solvent, in one- or multistep processes, and possibly at different temperatures, are described in the literature [ 35 ]. In untargeted plant metabolomics, methanol–water mixtures with or without acidification (e.g., formic or acetic acid) have become popular extraction solvents, since they allow extracting a wide range of metabolites [ 36 ]. For lycopene extraction, a mixture of methanol and chloroform (80:20, v / v ) was also reported [ 37 ].…”
Section: Metabolomics Platform In Plant Sciencesmentioning
confidence: 99%